La inteligencia artificial con enfoque al derecho de propiedad intelectual ecuatoriano - Benalcázar Pozo, Anthony Raúl (2025)
Artificial Intelligence progress has challenged the traditional legal framework in Ecuador, especially in the private intellectual property basis; for this reason, this article analyzes the legal challenges that AI situation provides, based on the ownership and authorship of works generated by artificial intelligence, an area not properly covered by current regulations in Ecuador. The methodology used was qualitative, using interpretation and comparative methods to analyze international norms and other relevant cases, such as Thaler and DABUS, Zarya of the Dawn and different regulations in multiple countries such as China, Japan and Mexico, identifying criteria such as hybrid authorship and algorithmic traceability as potentially applicable models in Ecuador, highlighting that while some countries are taking important steps towards the integration of AI within their Laws, legal gaps still exist which limit the acknowledgement and protection of works generated by artificial intelligence.